Development Of a Management Model for Enhancing the Quality Education Toward Sustainable Development of Vocational Colleges in Yunnan Province, China - Yunpeng, Zhao; Chiwpreecha, Kesinee (Journal of Dhamma for Life, 2026)
This research aimed to develop a sustainable development model for enhancing the quality of vocational education in Yunnan Province, China. A mixed-methods research design was employed. The quantitative phase involved 514 vocational education teachers selected as the study sample, while the qualitative phase consisted of a focus group discussion with nine experts to validate and refine the proposed model. Data were collected using a structured questionnaire and a focus group protocol. Quantitative data were analyzed using percentage, mean, standard deviation, and the Modified Priority Needs Index (PNI Modified), whereas qualitative data were analyzed through content analysis to support the development of the model. The findings revealed that the current state of sustainable development in vocational education was at a moderate level, whereas the desirable state was at a high level. The Modified Priority Needs Index indicated that all three dimensions of sustainable development required further improvement, with the highest priority assigned to economic sustainability, followed by social sustainability and environmental sustainability. Based on these findings, a sustainable development model for enhancing the quality of vocational education was developed. The model comprises four interrelated components: (1) the model title, (2) the principles, concepts, and objectives of the model, (3) the key components of the model, and (4) implementation guidelines. The model was subsequently evaluated by experts and found to demonstrate high levels of suitability and feasibility for application in vocational education institutions. The proposed model provides practical guidance for promoting sustainable development and improving the quality of vocational education in Yunnan Province.